Slow-tight binding inhibition of pepsin by an aspartic protease inhibitor from streptomyces sp MBR04 - Menon, Vishnu; Rao, Mala (International Journal of Biological Macromolecules, 2012)
The present article reports a low molecular weight aspartic protease inhibitor from a Streptomyces sp. MBR04 exhibiting a two-step inhibition mechanism against pepsin. The kinetic interactions revealed a reversible, competitive, slow-tight binding inhibition with an IC50 and K-i values of 4.5 nM and 4 nM respectively. The conformational changes induced upon inhibitor binding to pepsin was monitored by far and near UV analysis, demonstrated that the inhibitor binds to the active site and causes inactivation. Chemical modification of the inhibitor with WRK and TNBS abolished the antiproteolytic activity of the inhibitor. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Aspartic protease inhibitor; Low molecular weight; Slow-tight binding inhibition